Donor modification of thermally activated delayed fluorescence photosensitizers for organocatalyzed atom transfer radical polymerization. Issue 26 (24th June 2022) - Polgar, Alexander M.; Huang, Shine H.; Hudson, Zachary M.
Abstract : TADF donor-acceptor conjugates were applied as photosensitizers for organocatalyzed organic atom transfer radical polymerization. A donor-modification strategy was found to dramatically improve the control over the polymerization. Abstract : Thermally activated delayed fluorescence (TADF) photosensitizers based on 9, 10-dihydro-9, 9-dimethylacridine/2, 4, 6-triphenylpyrimidine conjugates with strong visible absorption, large excited state reduction potentials, and long-lived triplet excited states were successfully employed in the organocatalyzed atom transfer radical polymerization (O-ATRP) of methacrylic monomers. A donor-modification strategy dramatically improved the stability of the photocatalyst radical cations, while retaining their high oxidizing strengths, a key requirement for controlled O-ATRP. Time-resolved photoluminescence studies of the catalysts support initiation by electron transfer from both singlet and triplet states, with functionalized donors producing higher driving forces for photoinduced electron transfer. A donor-modified TADF photocatalyst was found for the synthesis of methacrylic polymers with Đ below 1.3 at catalyst loadings down to 50 ppm. This catalyst was also successfully applied in block copolymer synthesis, while the unfunctionalized analogue yields entirely uncontrolled polymerization.